Use of Hypnosis and Sensory Motor Stimulation To Aid Children with Learning Problems. - Jampolsky, Gerald G. (Journal of Learning Disabilities, 1970)
Data are presented which indicate that the combined use of hypnosis and sensory substitution for visual input may be beneficial to children with learning problems. Such techniques have been applied to children with the specific learning problem of number reversals. Following an initial session of hypnosis and two weeks of specific teaching procedures, five children in an experimental group had the total number of reversals reduced from an initial 10 to zero. For five children in the control group, without hypnosis or special training, number reversals increased from a total of 8 to a total of 13 over a two-week period. Neurological and psychiatric evaluation indicated that all children in both groups had learning disabilities which could be considered developmental, presumably resulting from a maturational lag of the nervous system.